Synthesis, characterization, and microwave absorbing performance of Mg0.8Zn0.1Co0.1Fe2O4 /CTO nanocomposite in 8–18 GHz frequency range - Sani, Yusuf; Azis, Raba’ah Syahidah; Ismail, Ismayadi; Yaakob, Yazid; saad, Nor Kamilah (Springer, 2024)
In this research, we have presented a novel composite that is both low-cost and highly efficient. This composite is synthesized by combining Mg0.8Zn0.1Co0.1Fe2O4 and Calcium Titanium Oxide (CTO) through a two-stage hydrothermal and coprecipitation process. The electromagnetic characteristics of the nanocomposites are effectively tuned by combining magnetic (MZCFe2O4) nanoferrite with dielectric (CTO) nanoparticles. XRD images showed that all prepared nanocomposites formed spinel structures without secondary phases. The findings of the structural and magnetic concepts and experimental investigations exhibit good agreement, confirming the accuracy of the cation distribution. The experimentally measured lattice parameter for MZCFe2O4 falls within the range of 8.3539–8.3874 Å, whereas the theoretical lattice parameter falls within the range of 8.3882–8.3833 Å. The mean crystal size was determined using the Debye–Scherrer technique, which was discovered to be between 53 and 75 nm, proving that all nanocomposites are nanocrystalline. The nanocomposite structure is shown in the FESEM micrographs, which show rocky-shaped particles with a range of hole sizes. All molecular elements are present, according to EDX bands. Mg0.8Zn0.1Co0.1Fe2O4 /CTO (S3) nanocomposites exhibit a peak reflection loss (RL) value of -23.05 dB (99.50% absorption) at 11.4 GHz. This level of absorption is achieved with a material thickness of 2 mm and maintains effective absorption (RL ≤ 10 dB) across a bandwidth of 2.5 GHz, spanning from 11 to 13.5 GHz. The ternary composites created in this study demonstrate a significant enhancement in microwave absorption capabilities. This improved performance is credited to the innovative structural arrangement, featuring robust interfacial polarization, multiple reflections, impedance matching, and a beneficial synergistic interaction between Mg0.8Zn0.1Co0.1Fe2O4 and CTO nanoparticles. This shows that S3 nanocomposite is a perfect candidate for high-efficiency microwave absorption. As a consequence, this method may be used to create a novel, highly effective microwave absorber.